Analiza stanja in možnosti ukinitve nadomestil za včlanitev v slovenske splošne knjižnice - Vodeb, Gorazd (Knjižnica, 2010)
The article presents the status and possibilities for abolition of user fees in Slovenian public libraries. Key international documents IFLA/UNESCO Public Library Manifest and Guidelines for Public Library Service define professional position on this issue. Pete Giacoma elaborates user fees from different perspectives such as economic theories, political consensus and equity. Legal framework for user fees in Slovenia is described and the study draws attention to its inconsistency. The legal framework, level of membership fees, percentage of registered borrowers etc. are compared with several European countries. Data on user fees in Slovenian public and academic libraries, museums and galleries were collected and compared. Differences among public libraries are shown regarding the structure and level of general income and income from user fees. Structure of expenditure is also presented and potential loss of income is assessed. Library directors expressed their views on consequences of proposed membership fee elimination. The survey ends with the proposal for next action steps towards successful governance of this problem.
Keywords: splošne knjižnice; članarine; uporabniki; finančna sredstva; Slovenia; Slovenija